2018
DOI: 10.1101/452201
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of mutation rate and selection at linked sites on fine-scale DNA variation across the homininae genome

Abstract: DNA diversity varies across the genome of many species. Variation in diversity across a genome might arise from regional variation in the mutation rate, variation in the intensity and mode of natural selection, and regional variation in the recombination rate. We show that both non-coding and non-synonymous diversity are positively correlated to a measure of the mutation rate and the recombination rate and negatively correlated to the density of conserved sequences in 50KB windows across the genomes of humans … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 87 publications
2
7
0
Order By: Relevance
“…Interestingly, there is a negative, but very shallow, correlation between the fraction of weakly deleterious mutations (210 , S d # 21) and N e ( Figure 3D and Table 3). This is consistent with a recent work that found that the effect of linked selection (mainly background selection) on genetic diversity is very similar along the genomes of great apes (Castellano et al 2018b).…”
Section: Model Choicesupporting
confidence: 93%
“…Interestingly, there is a negative, but very shallow, correlation between the fraction of weakly deleterious mutations (210 , S d # 21) and N e ( Figure 3D and Table 3). This is consistent with a recent work that found that the effect of linked selection (mainly background selection) on genetic diversity is very similar along the genomes of great apes (Castellano et al 2018b).…”
Section: Model Choicesupporting
confidence: 93%
“…Interestingly, there is a negative, but very shallow, correlation between the fraction of weakly deleterious mutations (10 < S d ≤ 1) and N e (Figure 3 D, Table 4). This is consistent with a recent work that found that the impact of linked selection (mainly background selection) on genetic diversity is very similar along the genomes of great apes (Castellano et al 2018b). Table 5 E).…”
supporting
confidence: 93%
“…Locally elevated mutation rate is a potential confound [53], however. Some evidence suggests that mutation rate correlates with substitution rates between species within long segments of the genome (~50 kb) [54], perhaps due to mutation pressure. However, the situation remains unclear, as other studies found that mutation rate does not explain variation in divergence between species [55,56].…”
Section: Discussionmentioning
confidence: 99%